Risk factors associated with the prevalence of Listeria monocytogenes in manured soils on certified organic farms in four regions of the United States - Chandler-Khayd, Carolyn; Di Francesco, Juliette; Baron, Jerome N.; Ramos, Thais De Melo; Aminabadi, Peiman; Jay-Russell, Michele T.; Haghani, Viktoria; Millner, Patricia D.; Pagliari, Paulo H.; Hutchinson, Mark; Kenney, Annette; Hashem, Fawzy; et al. (Frontiers in Sustainable Food Systems, 2023)
Introduction Biological soil amendments, including raw or untreated manure, are currently used to improve soil fertility, especially in organic operations that prohibit use of synthetic fertilizers. However, addition of untreated manure may pose a risk of contamination of fresh produce by pathogens of public health significance, including Listeria monocytogenes. Organic growers follow United States Department of Agriculture (USDA) National Organic Program regulations for raw manure use, which stipulate that harvest should commence no earlier than 90- or 120-days post-application, depending on direct contact between the edible portion of the produce and the soil. To inform the protection that such time-intervals provide, this study explored the farm-level risk factors associated with L. monocytogenes prevalence in USDA-certified organic farm soils amended with untreated manures. Methods A longitudinal, multi-regional study was conducted on 19 farms in four states (California, Minnesota, Maine, and Maryland) over two growing seasons (2017 and 2018). Untreated manure, soil, irrigation water, and produce samples were collected and cultured for L. monocytogenes. Mixed effect logistic regression was used to investigate risk factors associated with L. monocytogenes prevalence in soil. Results and Discussion Results showed that multiple factors influenced the odds of a soil-positive sample, including temporal [year (OR = 0.19), sampling day (OR = 0.09–0.48)] and weather-related [temperature range (OR = 0.48)] variables, manure characteristics [season of application (OR = 0.04, summer), presence of L. monocytogenes (OR = 2.89) and other pathogens in manure (OR = 5.24)], farm management factors [water source (OR = 2.73, mixed), number of year-round staff (OR = 0.02)], and soil characteristics [concentration of generic Escherichia coli (OR = 1.45), moisture (OR = 0.46), organic matter (OR = 7.30), nitrate (OR = 3.07), potassium (OR = 0.09) and calcium (OR = 2.48)]. This study highlights the complexity of L. monocytogenes prevalence in soil and contributes science-based metrics that may be used when determining risk-mitigation strategies for pathogen contamination.